A Study of the Potential of Community - Based Tourism Routes: Case Study of Silaphet Community, Pua District, Nan Province - Sertsri, Suthee; Srilachai, Atchara; Anekjumnongporn, Pongsavake (Journal of Multidisciplinary Academic Research and Development (JMARD), 2025)
The objectives of this research article were to 1) study the context of Silapetch Community, Pua District, Nan Province, and 2) study the potential of community-based tourism routes of Silapetch Community, Pua District, Nan Province. Data were collected from stakeholders in the tourism teams by in-depth interviews, observation, and the secondary data sources for evaluation and analysis. The research findings revealed the context and potential of Silapetch Community, Pua District, Nan Province which has interesting natural attractions, namely the Silapetch Waterfall and Doi Phu Kha National Park and it has the potential to welcome tourists such as tourism resources in the community, local culture and services with seven standardized homestays. For management potential, there are strong homestay leaders and someone who effectively engages members in community-based tourism management. The potential of marketing that is many tourists and bloggers are interested in reviewing but there are still market restrictions in terms of the use of social media because the group’s leaders are elderly, which making it limited in use. The potential study of community-based tourism routes, there are potential routes divided into two routes; 1) Silapetch Community Nature Study Route and 2) Tai Lue tribe that tourists can travel to visit.